COMPENSATORY-ADAPTIVE MECHANISMS OF CHANGES IN THE ENDOTHELIAL SYSTEM IN MINERS OF KUZBASS (CLINICAL AND MORPHOLOGICAL ASPECTS) - Кан, Сергей Людовикович; Бондарев, Олег Иванович; Косовских, Андрей Александрович; Лукашев, Константин Владимирович; Золоева, Олеся Сергеевна; Екимовских, Александр Владимирович; Борщикова, Тамара Ивановна; Макаров, Денис Николаевич (Medicine in Kuzbass, 2022)
The aim of the research – study of the morphofunctional state of the endothelial system in miners with different experience of underground work. Materials and methods. The study of the functional state of the endothelium was carried out in 163 working miners, morphological data were obtained from the results of autopsy of 50 miners who died in man-made disasters Results. The severity of systemic lesions with pathomorphological changes in the hemodynamic system were characteristic of many internal organs and depended on the length of work experience. Endothelial dysfunction was manifested by pronounced and progressive fibroplastic processes in the internal organs leading to functional and then structural changes. Conclusion. On the basis of clinical and pathomorphological data, a negative effect of long-term exposure to intermittent exogenous hypoxia and unfavorable working conditions, in comparison with age-related changes, was established on the state of the endothelial system of underground miners, followed by the implementation of fibrosing regenerative processes.